Endometriosis and pain - Sobstyl, Małgorzata; Tkaczuk-Włach, Joanna; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
Endometriosis is a chronic disease concerning approximately 6-10% of women at the reproductive age. Pain is observed in 66% of patients. The mechanism of pain includes local inflammation, adhesions and prostaglandin production by endometriosis. Treatment should be started with administration of NSAIDs and/or oral contraceptives. If no effect is observed, laparoscopy or GnRH analogs administration should be considered. Other treatments include dienogest or IUD releasing levonorgestrel.